Differences in the Life Cycle and Growth of Plasmodium Knowlesi, Inui, Vivax, Malariae, Falciparum, Ovale - Lidiya Fatmaningsih; Nadia Azhar Samasta; Linda Octa (Yayasan Adra Karima Hubbi, 2024)
Plasmodium is a parasite that causes malaria in humans. Various Plasmodium species have differences in their life cycles and growth, which influence the clinical characteristics and management of malaria. This article explains the differences in the life and growth cycles of the six Plasmodium species most commonly found in humans, namely Plasmodium knowlesi, Plasmodium inui, Plasmodium vivax, Plasmodium malariae, Plasmodium falciparum, and Plasmodium ovale. Each species has differences in its life cycle, including pre-erythrocytic, erythrocytic, and extracellular duration. In addition, these differences also influence clinical symptoms, disease severity, and response to treatment. A thorough understanding of these differences is important for accurate diagnosis and effective treatment of malaria.